Asprosin, visfatin and subfatin as new biomarkers of obesity and metabolic syndrome - Ugur, K.; Erman, F.; Turkoglu, S.; Aydin, Y.; Aksoy, A.; Lale, A.; Yalniz, M. (Verduci Publisher, 2022)
OBJECTIVE: Metabolic syndrome (MetS) and obesity are important public health problems associated with adipose tissue mass. Asprosin, visfatin, and subfatin are new members of which fate in MetS and obesity has not been fully revealed yet. Thus, this study was to investigate the association between asprosin, visfatin, subfatin. and biochemical values, demographic data, and body composition measurement values in MetS patients with and without obesity. PATIENTS AND METHODS: Blood samples were taken from a total of 90 people, including 31 MetS patients with obesity. 29 MetS patients without obesity. and 30 healthy (control). Asprosin, visfatin. and subfatin were studied by the ELISA method. RESULTS: There was a negative correlation between asprosin and Body Mass Index (BMI) in the MetS + Obese group. The correlations between asprosin and urea and fasting insulin (FI) levels in the MetS group were positive and statistically significant (p < 0.05). While there was a statistically significant negative correlation (p < 0.05) between visfatin and BMI in the MetS + Obese group. the correlation with waist circumference in the MetS + Obese and MetS groups was statistically significant and negative (p < 0.05). There was a statistically significant negative relationship (p < 0.05) between aspartate aminotransferase value and visfatin. The results between visfatin values and asprosin and subfatin in all groups were significant (p < 0.05). CONCLUSIONS: There is a direct relationship between circulating amounts of asprosin, visfatin, and subfatin hormones and age, weight, height, diastolic blood pressure, high-density lipoprotein-cholesterol, aspartate aminotransferase. alanine transaminase, and creatinine. Therefore, asprosin, visfatin, and subfatin hormones are the new biomarkers of metabolic turbulence.
Keywords: Asprosin; Visfatin; Subfatin; Obesity; Metabolic syndrome